The Relationship Between Urban Air Pollution Exposure and Preeclampsia Risk in Third-Trimester Pregnant Women - Agustini, I Gusti Ayu Ratih (Mandalika Journal of Medical and Health Studies, 2025)
Preeclampsia is a serious pregnancy complication characterized by hypertension and proteinuria after 20 weeks of gestation. It is a leading cause of maternal and fetal morbidity and mortality worldwide. Various factors contribute to its development, including genetic predispositions and environmental influences such as air pollution. Urban areas, with their high levels of particulate matter and gaseous pollutants, are increasingly being recognized for their detrimental effects on maternal health. This study aims to analyze the relationship between exposure to urban air pollution and the risk of preeclampsia in third-trimester pregnant women. A quantitative observational approach is used, employing data from peer-reviewed journal articles published between 2020 and 2024. The analysis focuses on the correlation between air pollution exposure, especially fine particulate matter (PM2.5), nitrogen dioxide (NO2), and sulfur dioxide (SO2), and the incidence of preeclampsia. Findings from multiple studies indicate a significant association between elevated air pollution levels and an increased risk of preeclampsia, particularly among women exposed to high concentrations of PM2.5 during the third trimester. The evidence suggests that air pollution exacerbates vascular dysfunction, leading to increased blood pressure and placental circulation impairment, which are key factors in the development of preeclampsia. These results highlight the urgent need for public health interventions to reduce air pollution exposure in urban areas, especially for pregnant women in their third trimester.